Los usos de la caricatura como fuente de investigación en el ámbito periodístico - Camacho Domínguez, Adriam (2017)
Research in the field of communication, and mainly in the journalistic field, has a diversity of sources that are not exploited to their full extent by university students. The use of primary sources in the investigative processes of titling presents deficiencies in the selection of topics and sources and need to overcome the reductionist views that focus mainly on the interpretation of messages that the media like television transmit to the society. It is precisely in the context of this methodological debate that the present paper aims to analyze the value of the editorial caricature as a source for the study of states of opinion, identity formation, and political imaginaries. In turn, the text addresses different theoretical contributions made around the meaning of the image as a valid resource for interpretation and social criticism. From the methodological point of view, besides the bibliographic analysis, the Multimodal Critical Analysis of the caricature is used to unravel the message of the caricaturist and the speeches that are generated from his communicative act. In addition, the theoretical methods of analysis-synthesis and logical-historical were necessary to specify different aspects of each of the cartoons of the analyzed journals. The results allowed to evaluate the need to incorporate in the journalistic investigations the use of primary sources such as caricatures to deepen the investigative techniques and the historical, political and cultural knowledge of the students of the Journalism career of the Laica University VICENTE ROCAFUERTE of Guayaquil (ULVR).